Effects of mindfulness meditation on anxiety, depression, stress, and mindfulness in nursing students: a meta-analysis and trial sequential analysis of randomized controlled trials - Li Yu-Feng; Sun Wen-Xin; Sun Xiu-Jie; Sun Juan; Yang Dong-Mei; Jia Bei-Li; Yuan Bin (Sciendo, 2020)
The aim of this study was to assess the effectiveness of mindfulness meditation (MM) on anxiety, depression, stress and mindfulness in nursing students.